Writing signs : the Fatimid public text - Bierman, Irene A. (Online access: California Digital Library UC Press E-Books Collection, 1982-2004 (Open Access), 1998)
Explores the complex relationship between alphabet and language, as well as the ways the two elements are socially defined by time and place. The author focuses on the Eastern Mediterranean in the 6th-12th centuries, particularly Cairo's Fatimid dynasty of 969-1171.